2014
DOI: 10.1111/jfs.12096
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Study of the Potential Protective Role of Lactobacillus Strains by Acrylamide Binding

Abstract: Acrylamide is a chemical naturally formed in certain foods during processing and/or cooking at high temperatures. Scientific studies have indicated that significant dietary exposure to acrylamide poses a risk for several types of cancer and may have harmful effects to the nervous system in humans. Hence, methods that can contribute to reduce acrylamide exposure in foods are needed. Considering that specific lactic acid bacteria are able to remove a variety of foodborne mutagens, namely heterocyclic amines, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…At 0 hour, the amount of bound acrylamide was from 11.89 to 29.13%, depending on the strains and the maximum binding was observed in strains AC and SHI. It was proposed that binding was a rapid process and occurred passively on the bacterial surface (88). This is in accordance with the findings by Hernandez-Mendoza et al that observed aflatoxin B1 bound 15 to 58% at 0 hour (89).…”
Section: Binding Ability Of Labs and Probiotics To Acrylamidesupporting
confidence: 82%
See 2 more Smart Citations
“…At 0 hour, the amount of bound acrylamide was from 11.89 to 29.13%, depending on the strains and the maximum binding was observed in strains AC and SHI. It was proposed that binding was a rapid process and occurred passively on the bacterial surface (88). This is in accordance with the findings by Hernandez-Mendoza et al that observed aflatoxin B1 bound 15 to 58% at 0 hour (89).…”
Section: Binding Ability Of Labs and Probiotics To Acrylamidesupporting
confidence: 82%
“…The binding ability of strains was investigated at different pH levels (3, 5 and 8). The maximum binding at pH 8 was observed in the strain L334 while at pH 3, a substantial reduction in binding ability occurred (88). Similarly, Zhang et al (45) reported a more binding of pyrolyzed mutagen at pH 6 -7 as well as Hernandez-Mendoza et al that implied, L. reuteri NRRL 14171 and L. casei Shirota bound more effectively at pH 7 than pH 8 (89).…”
Section: Binding Ability Of Labs and Probiotics To Acrylamidementioning
confidence: 86%
See 1 more Smart Citation
“…The chromatographic procedure was followed according to previously reported by Serrano-Niño et al (2014) Briefly, the HPLC System (Waters®, Milford, MA) used for AA quantification consisted of a Waters® 600 quaternary pump with a solvent delivery system, a C18 ODS Spheri-5 column (220 nm x 4.6 mm, Supelco®, Belefonte, PA), and an UV-visible detector (Waters® 2487) set at 195 nm. All data were collected and processed using the Empower data acquisition software (Waters ® ).…”
Section: Quantification Of Aa By Hplcmentioning
confidence: 99%
“…Hence based on our finding that prebiotic supplements enhance the levels of Bifidobacteria among ACR exposed dams, we speculate this could play a predominant role in the observed protective effect. Further, it may also related to the reported in vitro potential of specific Lactobacillus strains to bind the neurotoxin ACR which may result in increased detoxification [77]. Accordingly it is likely that the prebiotic supplements may affect the bioavailability of ACR.…”
Section: Discussionmentioning
confidence: 87%